Кримінологічна оцінка функціональності економічної злочинності - Мельничук, Тетяна Володимирівна; Мельничук, Татьяна Владимировна; Mel'nichuk, Tat'jana (Одеса : Юрид. л-ра, 2012)
The article is devoted to contemporary theory and practice of functional economic crime through the lens of criminological science. Thanks to the designation of the basic mechanisms and effects of hadow and criminal economic relations functional significance of economic crime in modern society, as well as the ability to use the acquired knowledge in preventive activities are revealed.
Мельничук Т. В. Кримінологічна оцінка функціональності економічної злочинності / Т. В. Мельничук // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 514-520.
Keywords: економічна злочинність; функції злочинності; структурно-функціональний аналіз; экономическая преступность; функции преступности; структурно-функциональный анализ; economic crime; crime functions; structure-function analysis